Comparison of Pudendal Nerve Block and Spinal Anesthesia in Proctological Surgeries: Efficacy, Safety, and Patient Outcomes - Samet Şahin; Cenk Yazkan; Özcan Dere; Ilgaz Kayılıoğlu; Önder Özcan (Medicina, 2024)
Background and Objectives: The selection of an appropriate anesthesia method is a critical factor in the surgical treatment of proctological diseases, significantly impacting patient outcomes and comfort. Pudendal nerve block (PNB) and spinal anesthesia (SA) are commonly employed in these surgeries, yet the optimal choice between the two remains debated. This study aims to compare the efficacy and safety of PNB and SA in patients undergoing surgical treatment for various proctological conditions, with a focus on postoperative pain management, functional outcomes, and complication rates. Materials and Methods: A prospective observational study was conducted on 590 patients who underwent proctological surgery under either PNB (n = 435) or SA (n = 155). Pain levels were assessed using the Visual Analog Scale (VAS), while functional outcomes were measured using the World Health Organization Disability Assessment Schedule (WHODAS 2.0). Statistical analysis was performed to compare the outcomes between the two groups. Results: Patients in the PNB group reported significantly lower postoperative VAS scores compared to those in the SA group, particularly in hemorrhoidectomy and laser hemorrhoidoplasty procedures. The PNB group also demonstrated superior functional outcomes, with lower postoperative WHODAS 2.0 scores and a reduced incidence of urinary retention compared to the SA group. Furthermore, the duration of surgery and hospital stay were significantly shorter for patients in the PNB group. Conclusions: The findings suggest that PNB may offer advantages over SA in proctological surgeries, particularly in terms of pain management, functional recovery, and reduced complication rates. PNB should be considered a viable alternative to SA, particularly in cases where rapid recovery and minimizing complications are priorities. Exceptions to this include specific proctological surgeries, such as those for malignant tumors in the region, complex anal fistulas, proctological conditions arising from inflammatory bowel diseases, and patients on immunosuppressive therapy. Further research is needed to confirm these results and optimize anesthesia selection in this context.